Long non-coding RNA AC099850.4 correlates with advanced disease state and predicts worse prognosis in triple-negative breast cancer - Vishnubalaji, Radhakrishnan; Alajez, Nehad M. (Frontiers in Medicine, 2023)
Our understanding of the function of long noncoding RNAs (lncRNAs) in health and disease state has evolved over the past decades, due to the many advances in genome research. In the current study, we characterized the lncRNA transcriptome enriched in triple negative breast cancer (TNBC, n=42) and estrogen receptor (ER+, n=42) breast cancers, compared to normal breast tissue (n=56). Given the aggressive nature of TNBC, our data revealed selective enrichment of fifty-seven lncRNAs in TNBC. Among those, AC099850.4 lncRNA was chosen for further investigation where it exhibited elevated expression, which was further validated in a second TNBC cohort (n=360) where its expression correlated with worse prognosis. Network analysis on AC099850.4high TNBC highlighted enrichment in functional categories indicative of cell cycle activation and mitosis. Ingenuity pathway analysis on the differentially expressed genes in AC099850.4high TNBC revealed activation of the canonical Kinetochore Metaphase Signaling Pathway, Pyridoxal 5'-phosphate Salvage Pathway, and Salvage Pathways of Pyrimidine Ribonucleotides. Additionally, Upstream regulator analysis predicted activation of several upstream regulator networks including CKAP2L, FOXM1, RABL6, PCLAF, and MITF, while upstream regulator networks of TP53, NUPR1, TRPS1, and CDKN1A were suppressed. Interestingly, elevated expression of AC099850.4 correlated with worse short-term relapse-free survival (log-rank p = 0.01). Taken together, our data is the first to reveal AC099850.4 as unfavorable prognostic markers in TNBC, associated with more aggressive clinicopathological features and suggest its potential utilization as prognostic biomarker and therapeutic target in TNBC.